Transformasi Lembaga Pendidikan Islam Tradisional di Madura dalam Perspektif Sejarah - Rahem , Zaitur (JOIES (Journal of Islamic Education Studies), 2017)
Transformation, institution, Islamization of the island of Madura, in tracking history was allegedly coincided with the current of Islamization of the island of Java. This can be seen from the evidence of Islamic artifacts on traditional symbols and educational institutions that still exist today. that is, in the form of congop, wekap, kobung, and langgar. This Islamic educational activity facility is considered as one of the requirements to provide a synthesis of the Islamization that enters the island of Madura. Although through a very long process, from the traditional educational institutions that a number of educational institutions and Islamic communities on the island of Madura can exist to this day. Traditional.